Sodium Ion-Driven Serine/Threonine Transport in Porphyromonas gingivalis - Dashper, S. G. (American Society for Microbiology, 2001)
Porphyromonas gingivalis is an asaccharolytic, gram-negative bacterium that relies on the fermentation of amino acids for metabolic energy. When grown in continuous culture in complex medium containing 4 mM (each) free serine, threonine, and arginine, P. gingivalis assimilated mainly glutamate/glutamine, serine, threonine, aspartate/asparagine, and leucine in free and/or peptide form. Serine and threonine were assimilated in approximately equal amounts in free and peptide form. We characterized serine transport in this bacterium by measuring uptake of the radiolabeled amino acid in washed cells of P. gingivalis energized with a tetrapeptide not containing serine. Serine was transported by a single system with an affinity constant for transport (K(t)) of 24 μM that was competitively inhibited by threonine. Serine transport was dependent on sodium ion concentration in the suspending buffer, and the addition of the ionophore gramicidin caused the inhibition of serine uptake. Together these data indicate that serine transport was sodium ion-motive force driven. A P. gingivalis gene potentially encoding a serine transporter was identified by sequence similarity to an Escherichia coli serine transporter (SstT). This P. gingivalis gene, designated sstT, was inactivated by insertion of a Bacteroides tetQ gene, producing the mutant W50ST. The mutant was unable to transport serine, confirming the presence of a single serine transporter in this bacterium under these growth conditions. The transport of serine by P. gingivalis was dependent on the presence of free cysteine in the suspension buffer. Other reducing agents were unable to stimulate serine uptake. These data show that P. gingivalis assimilates free serine and threonine from culture media via a cysteine-activated, sodium ion-motive force-driven serine/threonine transporter.